Retrospective analysis of the effect of angiotensin II receptor blocker versus β-blocker on aortic root growth in paediatric patients with Marfan syndrome. Issue 3 (22nd November 2013) - Mueller, Goetz C; Stierle, Lydia; Stark, Veronika; Steiner, Kristoffer; von Kodolitsch, Yskert; Weil, Jochen; Mir, Thomas S
Abstract : Objectives: Cardiovascular pathology, including aortic root dilation at the level of sinus of Valsalva (SV), is one of the major causes of morbidity in paediatric patients with Marfan syndrome (MFS). β-Blocker (BB) is well established to slow aortic dilation in MFS. Less is known about the effectiveness of angiotensin II receptor blocker (ARB) on aortic dilation in paediatric patients with MFS. Methods: 215 patients with MFS (9.01±5.7 years) were subject to a standardised diagnostic programme. Aortic root dilation was evaluated and followed up by echocardiography. In 48 cases, BB and ARB effects on aortic root dilation were evaluated. Effect of treatment was measured by comparison of z scores of SV before and after treatment initiation. Results: Treatment by ARB and BB leads to significant reduction of SV dilation (p<0.05). The deviation of SV enlargement from normal as expressed by the rate of change in z scores was significantly reduced by a mean difference of −0.56±0.71 z scores (p<0.001) under ARB therapy and by a mean difference of −0.35±0.68 z scores (p<0.05) under BB therapy. The prophylactic effect of ARB and BB on aortic root dilation is similar in both groups (p>0.05). Conclusions: Both concepts lead to a significant reduction of SV dilation. The effect of ARB and BB is similar. This is the first study concerning the comparison of ARB and BB in previously untreated paediatric patients with MFS. The results of the study show that both treatment strategies are beneficial in paediatric and adolescent patients.